Validity and reliability of the ACL21 for evaluating online collaborative learning - Palacios-Núñez, Madeleine Lourdes (2023)
Online collaboration contributes to the achievement of relevant learning such as learning to know, do, be and live together. Therefore, a new instrument (ACL21) is proposed to measure the online collaborative work of higher education students, based on the Collaborative Learning model and the Online Collaborative Learning model. The aim is to determine the validity and reliability of the Online Collaborative Learning Questionnaire 21 - ACL21. For this purpose, an Exploratory Factor Analysis (EFA) was carried out on a sample of 214 students. Subsequently, a Confirmatory Factor Analysis (CFA) was applied in a sample of 305 students to corroborate the structure of the model found in the EFA. It is found that the ACL21 is grouped into 2 factors called online group performance and online individual commitment. The ACL21 showed excellent internal consistency (Cronbach's alpha = 0.945). Regarding the AFC, the items are appropriately grouped into the factors found in the EFA. Therefore, the ACL21 is a valid and reliable instrument that allows diagnosing students' online collaboration. Thus, the results obtained by applying the ACL21 will allow teachers to design personalized training plans for their students to generate better conditions for online collaboration.